Connections with investment banks and their value: Evidence from seasoned equity offerings - Dou, Ying; Merkoulova, Yulia; Wu, Betty (Journal of Banking & Finance, 2025)
External networks are usually believed to add value, but what happens when the connected parties have conflicting interests in a transaction? We study the impact of social connections between seasoned equity offering (SEO) issuers and their lead underwriters on SEO outcomes. We find that, during accelerated offerings, connected issuers profit substantially from their links to investment banks through both lower direct issuance costs and smaller SEO discounts. Results of an event study based on the sudden collapse of Lehman Brothers show that the effect of connections is causal. We present evidence supporting an information flow hypothesis that connections improve deal outcomes by facilitating more efficient information exchange.